2013
DOI: 10.1136/thoraxjnl-2013-203557
|View full text |Cite
|
Sign up to set email alerts
|

Combination of budesonide/formoterol on demand improves asthma control by reducing exercise-induced bronchoconstriction

Abstract: BackgroundIn mild asthma exercise-induced bronchoconstriction (EIB) is usually treated with inhaled short-acting β2 agonists (SABAs) on demand.ObjectiveThe hypothesis was that a combination of budesonide and formoterol on demand diminishes EIB equally to regular inhalation of budesonide and is more effective than terbutaline inhaled on demand.MethodsSixty-six patients with asthma (>12 years of age) with verified EIB were randomised to terbutaline (0.5 mg) on demand, regular budesonide (400 μg) and terbutaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 29 publications
0
69
0
2
Order By: Relevance
“…One article was identi ed from the reference lists of included studies. Finally, three RCTs were included in the network meta-analysis 4,5,10 . The characteristics of these studies are shown in Table 1.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One article was identi ed from the reference lists of included studies. Finally, three RCTs were included in the network meta-analysis 4,5,10 . The characteristics of these studies are shown in Table 1.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Another RCT did not demonstrate a significant difference in efficacy for asthma control between NON-REG OD-ICS / FABA and an OD-SABA without any regular treatment NON-REG OD-SABA 5 . An RCT in patients with moderate asthma showed the inferiority of NON-REG OD-ICS / FABA for asthma control relative to regular ICS with a long-acting beta-2 agonist LABA plus OD-SABA REG-ICS / LABA OD-SABA 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Several previous RCTs have assessed the efficacy of OD-ICS / FOBA compared with conventional best practice in patients with mild or moderate asthma [4][5][6] . One RCT demonstrated the non-inferiority of on-demand beclomethasone with albuterol without any regular treatment relative to regular beclomethasone plus on-demand albuterol in mild asthma 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials RCTs have shown that on-demand use of an ICS and fastonset beta-2 agonist FOBA , such as a short-acting beta-2 agonist SABA or formoterol, without any regular treatment OD-ICS / FOBA is effective and might be an alternative therapy to regular ICS plus SABA REG-ICS OD-SABA or regular ICS / LABA plus on-demand SABA REG-ICS / LABA OD-SABA in patients with mild to moderate asthma 4,5 . Another RCT showed the non-inferiority of on-demand use of beclomethasone in combination with albuterol without any regular treatment, relative to regular low-dose beclomethasone plus on-demand albuterol with or without regular albuterol 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation